Upaya Meningkatkan Kemampuan Berpikir Kritis Siswa dalam Pembelajaran Sejarah melalui Strategi Go To Your Post - Siti Rohani; Yeni Kurniawati Sumantri (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
This article is entitled “The application of Go To Your Post Learning Strategies to Improve Students Critical Thinking Ability in Learning History” (Classroom Action Research of grade XII IPS 1 in 15 Senior High School in Bandung)”. The main problem in this research is how to improve the critical thinking skills of grade XII IPS 1 Senior High School 15 Bandung student, by using the Go To Your Post strategy in history learning. The method used in this study is the Classroom Action Research (CAR) method. The procedure carried out in this class action research refers to the Kemmis and Mc. Taggart starts with planning, action, observation and reflection. The subject in this study is students from grade XII IPS 1 in 15 Senior High School in Bandung, while the instruments used in data collection techniques were observation, interviews, field notes and documentation studies. The results showed that learning history by applying the Go To Your Post strategy can elevate students’ critical thinking skills because students are faced with situations that encourage them toward problem-solving, through group discussions and class discussions. The implementation of this learning strategy can conditioning an active and critical learning.